Pengaruh Kebijakan Investasi, Kebijakan Pendanaan dan Kebijakan Dividen terhadap Nilai Perusahaan: - Foreski, Anggun; Thamrin, Kemas Muhammad Husni; Andriana, Isni (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
When one policy is taken it will affect other financial decisions so that it will have an impact on company value. The company value which is relatively stable and tends to increase can attract the attention of investors who are oriented towards improving their welfare. If the value of the company is higher, the prosperity received by the owner of the company will be even greater. This study aims to determine the influence of investment policies, funding policies and dividend policies on company value (case study on food and beverage sub- sector manufacturing companies listed on the Indonesian stock exchange for the 2017-2021 period). The population in this study is all food and beverage sub-sector manufacturing companies listed on the indonesian stock exchange. The selection of samples was carried out by the purposive sampling method, and 23 companies were obtained. The data analysis technique used in this study is a multiple linear regression method with panel data. The results showed that investment policies and funding policies affect the value of the company. Dividend policy negatively affects the value of the company. Keywords: Investment Policies, Funding Policies, Dividend Policy